Transient Overcurrent Quantification Method of Grid-Forming Inverter Under Large Disturbances - Cui, Boyuan; Huang, Liang; Loh, Poh Chiang; Blaabjerg, Frede (IEEE International Conference on Industrial Technology (Online), 2025)
Grid-forming inverters (GFM) are increasingly essential in future power systems with the growing penetration of renewable energy. However, the overcurrent problem of the grid-forming inverter under large disturbance has remained a focal point of research. Specifically, the overcurrent can be classified into two procedures: the transient overcurrent and the steady-state overcurrent. In terms of numerous papers, most of the existing articles tend to focus on the steady-state overcurrent and few of them touch the transient overcurrent procedure. Nevertheless, the transient overcurrent process is also worthy of attention. To fill this gap, this paper starts from the phase current perspective, quantifying the transient overcurrent through the solution of the differential equation under large disturbances including grid frequency drop, grid phase jump and grid voltage sag. Simulation results of the study system verify the accuracy of the theoretical quantifications of the transient overcurrent under large disturbances.